Analisis terhadap Model Layanan Mobile Banking pada Bank Syariah Indonesia dari Tinjauan Konsep Syariah - Annas Syamsu Fahmi Rizal; Ahmad Muqorobin; M Qoshid Al Hadi; Mohammad Syifa Urrosyidin (Tathawwur: Jurnal Ekonomi Pembangunan dan Keuangan Islam, 2025)
During the post-COVID-19 pandemic recovery period, rapidly developing information technology in recent years has directed the focus of several banks towards digital services, including through mobile banking applications. The rapid growth of the internet has changed the way companies connect with customers, as well as the banking business in Indonesia. The concept of "blessing" (barakah) must remain a priority for every Muslim, especially in financial institutions like banks. This paper aims to examine and analyze the mobile banking service model available on the BSI Mobile Banking application. In 2021, Bank Syariah Indonesia, also known as BSI, began merging three Islamic commercial banks in Indonesia. In order to support the development of information technology, particularly in the banking sector, BSI also created the BSI Mobile Banking application to facilitate transactions. The method used in this research is a qualitative study with a grounded research approach, also employing descriptive qualitative analysis methods. Although the service model in the BSI Mobile application has met customer needs and is in accordance with basic Sharia principles, many customers or members of the Muslim community have not used it to its full potential or are even unaware of the system or model and utilization of the mobile banking application. This could lead to the application not being used optimally. Based on the results of the research that the researcher has written, the existing BSI Mobile Banking service model should prioritize education and product socialization of BSI Mobile Banking, using methods that can provide understanding related to Islamic law concerning the principles of halal and haram. Regulations will be enforced due to legal threats and causes. It can be concluded that the wakalah contract in BSI Mobile Banking services is permissible in accordance with the conditions and pillars outlined in the DSN MUI Fatwa No. 10/DSN-MUI/VI/2000, and it aligns with the service model that operates in the use of the mobile banking application.